1999
DOI: 10.1007/bf02475507
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of oxidation of diols by ozone in aqueous solution

Abstract: The kinetics of the oxidation of diols by ozone was investigated by a speclrophotometric method in the temperature interval of 277-304 K. The activation parameters of the reaction were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Zimin et al , have investigated the ozone reactions of cyclopentanone, cyclohexanone, and methylbutylketone and the corresponding keto–enol equilibria. Low reactivities were found for the keto forms (see Table ).…”
Section: Nonradical Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zimin et al , have investigated the ozone reactions of cyclopentanone, cyclohexanone, and methylbutylketone and the corresponding keto–enol equilibria. Low reactivities were found for the keto forms (see Table ).…”
Section: Nonradical Reactionsmentioning
confidence: 99%
“…This finding is consistent with previous studies, which have also revealed low reactivities of ketones toward ozone. From their studies and the obtained keto–enol equilibria data, Zimin et al , concluded that both the keto and the enol tautomers of ketones react with ozone in the presence of an acid and that the importance of the enol reaction increases with increasing acid concentration. At higher acidities, the keto–enol equilibrium shifts toward the enol tautomer.…”
Section: Nonradical Reactionsmentioning
confidence: 99%
“…The kinetics of the reaction of ozone with alcohols was investigated by means of kinetic spectrophotometrical method described in [7]. When the reaction time was shorter than 2 min, the stopped-flow method was used.…”
Section: Methodsmentioning
confidence: 99%
“…Examination of the later time points demonstrated a significant loss of particle size and indicated that the PAA- co -PAAm shells underwent degradation after extensive ozone treatment. It has been reported in the literature that ozone can react with both amide , and ether , functionalities; both of which are integral portions of the shell structure. The 22% cross-linked sample shows a loss in size after 720 min (12 h) in the presence of ozone, indicating that breakdown of a portion of the material had occurred, whereas, the 72% cross-linked sample appeared to retain the nanostructural integrity after 12 h of ozone treatment.…”
mentioning
confidence: 99%
“…After 24 h, additional resonances within the 1 H NMR spectrum (Figure c) indicated that degradation had occurred to result in a mixture of products. The exact structures of these products were not determined, as there are several side reactions that are possible for both the amide and the ether functionalities. Although this model compound is a simplistic structure, relative to the nanocage, the demonstration of chemical instability serves to support degradation of the cross-linking units as the mechanism by which the nanocage fails at long exposure times to ozone.
5
…”
mentioning
confidence: 99%